ChopBAI: BAM index reduction solves I/O bottlenecks in the joint analysis of large sequencing cohorts. (18th March 2016) - Kehr, Birte; Melsted, Páll
Abstract : Summary: Advances in sequencing capacity have led to the generation of unprecedented amounts of genomic data. The processing of this data frequently leads to I/O bottlenecks, e. g. when analyzing a small genomic region across a large number of samples. The largest I/O burden is, however, often not imposed by the amount of data needed for the analysis but rather by index files that help retrieving this data. We have developed chopBAI, a program that can chop a BAM index (BAI) file into small pieces. The program outputs a list of BAI files each indexing a specified genomic interval. The output files are much smaller in size but maintain compatibility with existing software tools. We show how preprocessing BAI files with chopBAI can lead to a reduction of I/O by more than 95% during the analysis of 10 kb genomic regions, eventually enabling the joint analysis of more than 10 000 individuals. Availability and Implementation: The software is implemented in C ++, GPL licensed and available at http://github.com/DecodeGenetics/chopBAI Contact: birte.kehr@decode.is